FACTORS AFFECTING CSR DISCLOSURE IN CONSUMER GOODS INDUSTRY ISSUERS - Ningsih, Helis Safitri Purwanti; Silviani, Amanda Agnes; Br Butar-Butar, Chaira Astami Putri; Dinata, Candra; Azis, Fikri Abdul; Nawara, Shadiqin (Riau International Conference on Economics, Business and Accounting, 2024)
The company definitely wants to build a good image for the surrounding environment by giving it responsibility or what is called CSR. This study aims to determine the Effect of Government Share Ownership, Foreign Share Ownership, and Company Size on CSR disclosure in Consumer Goods Industry Issuers Listed on the Indonesia Stock Exchange in 2019-2021. The sample technique used in this study uses purposive sampling and the number of samples are 66 companies listed in the consumer goods industry that are listed on the IDX in 2019-2021. Data analysis using multiple linear regression analysis method with the SPSS 26 analysis application. The results of this study indicate that government share ownership has no effect on CSR disclosure, this is indicated by a significance value of 0.228, meaning that the significance value of 0.228 is greater than 0.05. Foreign share ownership has no effect on CSR disclosure, this is indicated by a significance value of 0.571, meaning that the significance value of 0.571 is greater than 0.05. Firm size has no effect on CSR disclosure, this is indicated by a significance value of 0.071, meaning that the significance value of 0.071 is greater than 0.05.